Catalysis and mechanistic insights on Sirtuin activation - Dittenhafer-Reed, Kristin E. (2010)
SIRT1 is a member of the Sir2 family of NAD(+) dependent protein deacetylases. The central role of SIRT1 in multiple metabolic and aging-related pathways has pushed SIRT1 to the forefront for the discovery of small molecule activators. Promising compounds including resveratrol and SRT1720 have been reported, however whether these compounds are direct activators and the mechanism by which they activate remains poorly defined. This review will examine the current debate surrounding purported activators, focusing on the assays used in screening compounds, Sirtuin catalysis and the mechanistic basis for their actions. We discuss the potential pathways of SIRT1 activation that could be exploited for the development of novel therapeutics for treating type II diabetes, neurodegeneration and diseases associated with aging.